Risk Analysis in E-Commerce (E-C) through the Method HAZOP (Hazard and Operability) - Patricia Simona LUP; Gabriela Ioana PROȘTEAN; Denisa PAP GHERASIM (Communications of International Proceedings, 2020)
This paper identifies the potential risks to which consumers are exposed when trading via e-commerce. In order to increase consumer confidence in e-commerce and get them to choose this method for future purchases, we must first understand where this lack of trust comes from, what are the potential risks, but also the dangers to which consumers are exposed, and only then to combat the risk in the E-C, by proposing concrete measures and developing such a necessary tool, through the HAZOP method.
Keywords: E-Commerce Risks; HAZOP; Risk Matrix; E-Commerce Risk Mitigation